EFEKTIVITAS PENERAPAN METODE GENIUS LEARNING DENGAN MEDIA LAGU RUMUS MATEMATIKA PADA MATERI LUAS TRAPESIUM DAN LAYANG-LAYANG - Faridah, Luluk; Nasihah, Faisatun (saintis, 2016)
The purpose of the study was to assess the effectiveness of Genius learning method application with math formula song media in the material of large of trapezoidal and kite in terms of: (1) Complete Learning; (2) Studentâs Activities, (3) Teacherâs activities, and (4) Studentâs Response. The subjects of the study were the students of class V MI Sunan Giri Gondanglor Sugio Lamongan in the academic year of 2013/2014. The data collection techniques used were observations, questionnaires and tests. Observation methods used to determine the activities of students and teachers during the learning process. The questionnaire method used to determine the students response to learning that has been done. While the test was used to determine the level of student learning in the classical completeness. Based on the survey results revealed that the method of Genius Learning with media effectively tune a mathematical formula applied to the material ofÂ  large of trapezoid and kites in terms of: (1) classical learning completeness of 90.91%; (2) the activity of students with the percentage of positive activity of students of 95.00%; (3) the teachers activities with the percentage of positive activity teacher at 96.43; and (4) the students response positive response of 89.088%. Given the results, it can be taken into consideration by all educators to try to implement Genius Learning method in learning activities.